Pengaruh Konflik Peran Dan Ketidakjelasan Peran Terhadap Kinerja Auditor Dengan Emotional Quotient Sebagai Variabel Pemoderasi - Cendana, Devy Kusuma; Suaryana, I Gusti Ngurah Agung (E-Jurnal Akuntansi, 2018)
Auditors are often confronted by potential role conflict and vagueness of roles thus affecting auditor performance. A person who has a good Emotional Quotient (EQ) can manage his emotions well so that he can better control himself if faced with role conflict and unclear role in performing his duties or role as an auditor so that the resulting performance tends to be better. This study aims to prove empirical evidence of the influence of pera conflict and unclear role on the performance of auditors and the role of emotional quotient in moderating the influence of role conflict and unclear role on the performance of auditors. This research was conducted at Public Accounting Firm in Bali with survey method using questionnaire instrument. The sample size of 72 respondents using the method of determining the saturated samples, and the questionnaire that can be analyzed by 43 analysis shows that role conflict negatively affect the auditor's performance, unclear role negatively affect the auditor's performance, emotional quotient weaken the influence of role conflict on auditor performance, and emotional quotient weakens the influence of unclear role on the auditor's performance. Keywords : Auditor performance, role conflict, role ambiguity, emotional quotient